Membangun Paradigma Konseling Masa Depan melalui Lensa Filsafat: Systematic Literature Review - Aziziyah, Astry Fauzian; Prasetya, Akhmad Fajar (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of guidance and counseling in the 21st century faces multidimensional challenges due to digitalization, cultural changes, and rapid social dynamics. This condition requires counselors to not only have technical skills but also reflective capacity rooted in a philosophical understanding of humans, knowledge, and values. This study aims to formulate a future counseling paradigm through a comprehensive philosophical approach by integrating the dimensions of ontology, epistemology, and axiology. The method used is a qualitative approach with a Systematic Literature Review (SLR) design on scientific articles from 2022–2026 discussing the relationship between philosophy and counseling. The study results show that philosophy serves as a conceptual foundation that shapes counselors’ perspectives on human nature, the sources of counseling knowledge, as well as the direction of values and service ethics. However, most studies still discuss philosophical dimensions partially and have not formulated an integrative paradigm. This study offers a holistic conceptual framework that positions philosophy as the main lens in developing a future counseling paradigm that is humanistic, reflective, adaptive, and responsive to social and technological challenges. This framework is expected to contribute to the development of theories, curricula, and counseling practices relevant to contemporary dynamics.